Climate Change and Rural Development in the Middle Atlas Mountains and Fringe Areas (Morocco) - Moulay-Driss El Jihad (Revue de Géographie Alpine)
In Morocco, studies on the relationship between climate change and rural development policies, especially in the mountains, are few and far between. This article takes a geopolitical approach to this particular issue in the Middle Atlas. Until the 1990s, rural development policies were based on the fight against forest degradation and soil erosion, first and foremost with a view to reducing dam silting. Since the early 2000s, efforts have focused on direct contact with the population in order to meet their needs. However, integration of the forestry sector into the agricultural system has not yielded the expected results. People, deeply concerned by the multifaceted impacts of climate change, have not been particularly receptive to sectoral proposals of projects related to forest heritage management. To address this concern, new development programs have been implemented and decentralised at the municipal level. Although projects still fall short of needs, the new approach to rural development is more territorial in terms of improving the resilience of populations to climate change at present and in the future.